Pengembangan Aplikasi untuk Pembelajaran Keterampilan Menulis Al - Qur'an dengan Pendekatan Gamification - Muhammad Afif Fauzi; Lutfi Fanani; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Indonesia has many reading Al - Quran events. for instance, reading Al - Quran competition, Quran Community or tadabbur Quran. But, not many people to know about writing Al - Quran, just a few certain people who know what else to do the activity, such as pesantren environment. even though, in writing Al - Quran activity there are few advantages, for instance, thoroughness training, patient training, and speed up reading Al - Quranskill. Indonesia a country with the largest Muslim population, but, not many peoples who to learn Al - Quran, for just taking time to read is very difficult. From these problems, this research wants to develop an application which to helps people learn Al - Quran especially in learning Al - Quran writing. In its development, this research also uses a gamification approach such as score collection, leaderboard, and high score. For the design phase produced eight sequence diagram and CRC Cards design, data design use Entity Relationship Diagram, algorithm design produced three algorithms and 12 prototypes design. The app specifically implemented for Android programming based on Java and using google firebase realtime database for the database Validation testing produced seven tests, where all of the test cases have produced a valid status. The result of usability testing is 70,5 percent. The comparison score result between the score app with Ustadz valuation has produced from ten data training nine often includes in the Ustadz valuation criteria.